مراحل و مححدات الاستخدام الدولي للعملة الاوربية الموحدة(اليورو) دراسة اقتصادية مقارنة - الصفار, احمد سليمان; حسن, خليل غازي (Sulaimani Journal for Humanities, 2000)
The purpose of this studyis to analyze the stages and the determinants of using the european sinle — currency (EURO)in the world markets. An analytical approach has been used in the analysis of some indicators concerning the economical characteristics and the mastrichtcriteria, which appeared from the data given from the several references. The analysis showed that the (EURO) will not influence the international monetary system in a short term .